2022
DOI: 10.1126/sciadv.abp8738
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution wearable electrotactile rendering system

Abstract: The human somatosensory system is capable of extracting features with millimeter-scale spatial resolution and submillisecond temporal precision. Current technologies that can render tactile stimuli with such high definition are neither portable nor easily accessible. Here, we present a wearable electrotactile rendering system that elicits tactile stimuli with both high spatial resolution (76 dots/cm 2 ) and rapid refresh rates (4 kHz), because of a previously unexplored current-steering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…In Experiment 4, we confirmed that the ratio of the pain threshold to the tactile threshold (dynamic range) was increased by the application of a local anesthetic cream, even with multipoint electrical stimulation. Multipoint electrical stimulation differs from single-point electrical stimulation in that it also enables the presentation of patterns and motion of these patterns [25]. Vection-like movements can be presented by electrical stimulation as a typical display pattern.…”
Section: E Experimentsmentioning
confidence: 99%
“…In Experiment 4, we confirmed that the ratio of the pain threshold to the tactile threshold (dynamic range) was increased by the application of a local anesthetic cream, even with multipoint electrical stimulation. Multipoint electrical stimulation differs from single-point electrical stimulation in that it also enables the presentation of patterns and motion of these patterns [25]. Vection-like movements can be presented by electrical stimulation as a typical display pattern.…”
Section: E Experimentsmentioning
confidence: 99%
“…Electro-tactile displays also allow for portable setups due to their simple mechanism (Cornman, et al, 2017). Some studies have used electro-tactile stimuli as wearable devices, presenting them to the fingertips and the entire palm (Lin, et al, 2022;Yao, et al, 2022). Takei et al (2015) attached a film pressure distribution sensor under a film electro-tactile display, measured the pressure applied to each electrode by a pressing finger, and used it as feedback for electrical stimulation.…”
Section: Electro-tactile Stimulationmentioning
confidence: 99%
“…With the emerging of metaverse, human-machine interaction (HMI) attracts more and more attentions as the indispensable element in metaverse, even robotics, VR/ AR and human-machine systems [1][2][3][4]. Current research on bio-organic interfaces has contributed significantly to the realization of HMI [5,6].…”
Section: Introductionmentioning
confidence: 99%